The effects of therapeutic horticulture on student well-being and academic resilience - Diehl, Elizabeth R. M.; Diehl, David C.; Tham, Siang Yu (Frontiers in Psychology, 2025)
IntroductionCollege students across the United States are struggling with significant and increasing levels of stress and anxiety, which contribute to both personal and academic distress. There is a growing need to develop and evaluate programs to reduce stress and anxiety and build resilience in students. The focus of this study was to explore the use of therapeutic horticulture (TH) with university students, specifically hypothesizing that participants would experience reductions in stress and anxiety and increases in resilience and academic resilience after participating in the program.MethodsFifty-one university students participated in at least eight weeks of therapeutic horticulture programming and completed pre- and post-surveys assessing participants’ perceived stress, state and trait anxiety, general resilience, and academic resilience. Paired sample t-tests were computed to determine if there was significant change on each outcome variable from the pre-survey to the post-survey.ResultsSignificant pre-post improvements in outcomes were found for: academic resilience, including perseverance, help seeking, and managing negative emotions; perceived stress; state and trait anxiety; and general resilience. Findings indicate that therapeutic horticulture is potentially beneficial across a variety of relevant outcomes.DiscussionThe findings indicate that therapeutic horticulture is a promising intervention model for improving mental health and academic outcomes for U.S. college students. These outcomes are critical for overall health and well-being, as well as academic performance, which contributes to lifelong positive outcomes. Future research should include strong study designs that include random assignment into conditions.